Peran Akuntansi Forensik dalam Mendeteksi Kecurangan Laporan Keuangan: Studi Literatur Review pada Jurnal Nasional - Nia Nafilah Andani; Ainun Arizah (AKUNTANSI 45, 2025)
Financial reports have a central role in providing reliable information to stakeholders, especially for companies that have gone public. However, these reports are vulnerable to fraudulent practices that can harm many parties. Forensic accounting is present as an investigative approach that is able to identify and reveal irregularities in financial reports. This study aims to examine the role of forensic accounting in detecting incidents through a systematic literature review of 21 scientific articles published between 2021 and 2025. The results of the study indicate that the effectiveness of forensic accounting in detecting fraud varies, depending on the industry sector, the methods used, and the context of investigating each study. In general, forensic accounting has been shown to make a significant contribution to uncovering financial report manipulation, strengthening internal controls, and encouraging transparency through collaboration with investigative audits and independent reporting systems. However, several studies note that the contribution of forensic accounting is not always direct to fraud prevention, but still has strategic value in supporting the audit and investigation process. These findings emphasize the importance of developing more comprehensive forensic accounting, especially in Indonesia, in order to improve the quality of financial reporting and strengthen the integrity of the financial system as a whole.